Penerapan Layanan Bimbingan Kelompok dalam Mencegah Kenakalan Remaja - Syahputra, Khairil; Romli, M. Edwar; Nurlela, Nurlela; Arizona, Arizona (Bulletin of Counseling and Psychotherapy, 2020)
The problem in this study is that there are often deviations in student behavior which results in students breaking the rules of discipline at school. Namely skipping school, often late, smoking and fighting. This study aims to determine whether the application of group counseling services in preventing the delinquency of juvenile students in SMA Negeri 9 Palembang effectively. The research method used is a quantitative approach with pre experimental methods with OneGroup Pretest and Posttest Design. The subjects of this study were students of class XI IPS 1 of SMA Negeri 9 Palembang with a sample of 10 students. From the results of data analysis shows that the total pretest value before treatment was 586 with an average of 58.6 and the results of the posttest after being treated with a value of 842 with an average of 84.2. Hypothesis testing results prove that the results of the t-test calculations where t-count = 5.039≥ t-table = 1.833. thus the application of group guidance services in preventing juvenile delinquency from students is effectively accepted.